Pembinaan Karakter Kajian Suroh Al-Furqon - Herawati Daulae, Tatta (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
Al-Qur'an is the word of God in the form of miracles, passed down to the Prophet Muhammad, through the angel Gabriel who read it into worship. Al-Qur'an is the first source in the teachings of Islam and is the main guide for every Muslim. In the Qur'an Surah Al-Furqon verses 63-77 outlined some of the good qualities that are the basis for character development, namely; humble heart, not repay bad behavior with the same bad, do night prayers, feel afraid of the punishment of hellfire, keep away from redundant and miserly behavior, avoid all forms of polytheism, do not commit acts that can eliminate the lives of others, do not commit adultery, repent, always maintain faith and do good deeds, do not give false testimony, do not follow useless or useless work, listen and receive good advice, pay attention to family safety and happiness, and be patient.